Development of a child with Joubert syndrome. - Torres, M. Carmen; Buceta, M. José; Cajide, Consuelo (The Spanish Journal of Psychology, 2001)
Sin resumen
Keywords: síndrome de Joube4 agenesia de vermis; atención temprana